Mucosal Immunity and B Cells in Teleosts: Effect of Vaccination and Stress - Parra, David; Reyes-Lopez, Felipe E.; Tort, Lluis (Frontiers in Immunology, 2015)
Fish are subjected to several insults from the environment, which may endanger animal survival. Mucosal surfaces are the first line of defense against these threats, acting as a physical barrier to protect the animal but also functioning as an active immune tissue. Thus, four mucosal-associated lymphoid tissues (MALTs), which lead the immune responses in gut, skin, gills, and nose, have been described in fish. Humoral and cellular immunity, as well as their regulation and the factors that influence the response in these mucosal lymphoid tissues, are still not well known in most fish species. Mucosal B-lymphocytes and immunoglobulins (Igs) are key players in the immune response that takes place in those MALTs. The existence of IgT as a mucosal specialized Ig gives us the opportunity of measuring specific responses after infection or vaccination, a fact that was not possible until recently in most fish species. The vaccination process is influenced by several factors, being stress one of the main stimuli determining the success of the vaccine. Thus, one of the major goals in a vaccination process is to avoid possible situations of stress, which might interfere with fish immune performance. However, interaction between immune and neuroendocrine systems at mucosal tissues is still unknown. In this review, we will summarize the latest findings about B-lymphocytes and Igs in mucosal immunity and the effect of stress and vaccination on B-cell response at mucosal sites. It is important to point out that a limited number of studies have been published regarding stress in mucosa and very few about the influence of stress over mucosal B-lymphocytes.